Fenomena Manajemen Pajak: Transaski Hubungan Istimewa Sebagai Variabel Moderasi - Siregar, Efrida; Khomsiyah, Khomsiyah (E-Jurnal Akuntansi, 2023)
The research aims to determine the effect of profitability, foreign ownership and leverage on tax management, with the moderating effect of special relationship transactions. A total of 75 companies in the raw and primary consumer goods sector on the Indonesia Stock Exchange for the 2019-2022 period were used as samples using the purposive sampling method. The analysis was carried out using a panel data regression model, which had previously been tested on classical assumptions. The research results show that profitability has a positive effect, while foreign ownership has a negative effect. Meanwhile, leverage has no effect. Special relationship transactions do not have a moderating role in the relationship between profitability and foreign ownership. However, it can weaken the influence of leverage. These findings highlight the complexity of internal and external factors that influence tax management practices. This research can provide guidance for practitioners and researchers in developing more effective tax management strategies. Keywords: Foreign Ownership; Leverage; Tax Management; Profitability; Special Relationship Transactions